No products in the cart.

( x-2) (x+1) = (x-1) (x+3)

CBSE, JEE, NEET, CUET

CBSE, JEE, NEET, CUET

Question Bank, Mock Tests, Exam Papers

NCERT Solutions, Sample Papers, Notes, Videos

( x-2) (x+1) = (x-1) (x+3)
  • 1 answers

Aarya Singh 3 weeks, 1 day ago

(x-2) (x+1) = (x-1) (x+3) 2x+x-2x-2 = 2x+3x-x-3 x-2 = x+3x-3 x-2 = 4x-3 x-4x = -3+2 -3x = -1 x = 1/3
http://mycbseguide.com/examin8/

Related Questions

What is the meaning of ****
  • 0 answers
13.1 prashnawali ka chodta Kishan
  • 1 answers
(x+2)^3=2x(x^2-1)
  • 1 answers
3/2x+5/3y=7,9x-10y=14
  • 0 answers
What is monomial
  • 0 answers

myCBSEguide App

myCBSEguide

Trusted by 1 Crore+ Students

Test Generator

Test Generator

Create papers online. It's FREE.

CUET Mock Tests

CUET Mock Tests

75,000+ questions to practice only on myCBSEguide app

Download myCBSEguide App